Közép-Európa nyomában... : viták, vélemények a régióról - Majoros, István (Közép-Európai Közlemények, 2009)
Discussions, opinions are presented about Central Europe in this study. First the author brings the 80s to mind when Milan Kundera published his study about Central Europe kidnapped form the West. After that the author presents his researches about this region. Some historiens (French and Hungarians), a member of the European Parliement and a menager were interviewed by the author in automn 2007 and in January 2008 and he summarizes his results in this study. It is difficult to say something about the future of this region. But these days Central Europe doesn’t work as a group in the European Union in spite of the fact that the region has common interests.